A Control Methodology for Building Energy Management Systems (BEMS) in Heat Networks with Distributed Generation. (October 2018) - Jones, Sean Rhys; Beardmore, John; Gillott, Mark; Boukhanouf, Rabah; Walker, Gavin
Abstract: Reducing building energy consumption is important to achieve sustainable development, as a result, there is a need to investigate better energy systems with well-designed management infrastructure. At the Creative Energy Homes, a low-temperature heat network with distributed generation links seven properties. The aim of the system is to investigate the efficiency benefits of low-temperature heating, while at the same time testing the prosumer concept. For homeowners to be prosumers, they can buy and sell heat to a network. This system is the first of its kind, and as a result required bespoke Building Energy Management Systems (BEMS). This paper focuses on the hardware, software, and system operation used as part of project SCENIC (Smart Controlled Energy Networks Integrated in Communities). The project utilises a simple and cheap hardware configuration involving relays, IO boards and RaspberryPi microcomputers. An open-source Building energy Management System (oBeMS) platform is used for monitoring and control.